Risk measurement and management during new product development: an exploratory study. (30th July 2008) - Szwejczewski, Marek; Mitchell, Rick; Lemke, Fred
Developing a new product involves risk. Several writers on the subject of product development have suggested various approaches for determining and managing risk. However, while much has been written about how firms should manage risk, there has been very little research regarding what companies are doing in practice. This paper seeks to rectify this situation by presenting the results of a research project that investigated how a number of UK manufacturing companies measure and manage risk during the New Product Development (NPD) process.